Biochemical, pharmacological and structural characterization of BmooMP-I, a new P–I metalloproteinase from Bothrops moojeni venom - Salvador, Guilherme H.M. [UNESP]; Borges, Rafael J. [UNESP]; Eulálio, Micaela M.C. [UNESP]; dos Santos, Lucilene D. [UNESP]; Fontes, Marcos R.M. [UNESP] (Elsevier, 2020)
Snakebite envenoming is still a worrying health problem in countries under development, being recognized as a neglected disease by the World Health Organization. In Latin America, snakes from the genus Bothrops are widely spread and in Brazil, the Bothrops moojeni is a medically important species. The pharmacological effects of bothropic snake venoms include pain, blisters, bleeding, necrosis and even amputation of the affected limb. Snake venom metalloproteinases are enzymes abundantly present in venom from Bothrops snakes. These enzymes can cause hemorrhagic effects and lead to myonecrosis due to ischemia. Here, we present BmooMP-I, a new P–I class of metalloproteinase (this class only has the catalytic domain in the mature form) isolated from B. moojeni venom. This protein is able to express fibrinogenolytic and gelatinase activities, which play important roles in the prey's immobilization and digestion, and also induces weak hemorrhagic effect. The primary sequence assignment was done by a novel method, SEQUENCE SLIDER, which combines crystallographic, bioinformatics and mass spectrometry data. The high-resolution crystal structure reveals the monomeric assembly and the conserved metal binding site H141ExxH145xxG148xxH151 with the natural substitution Gly148Asp that does not interfere in the zinc coordination. The presence of a structural calcium ion on the surface of the protein, which can play an important role in the stabilization of hemorrhagic toxins, was observed in the BmooMP-I structure. Due to the relevant local and systemic effects of snake venom metalloproteinases, studies involving these proteins help to better understand the pathological effects of snakebite envenoming.
Keywords: Bothrops moojeni; Fibrinogenolytic metalloproteinase; Hemorrhagic metalloproteinase; Snake venom P–I metalloproteinase